Pernikahan Adat Melayu Riau sebagai Jembatan Integrasi Nilai Islam dan Identitas Sosial Kontemporer - Dina Bahriani Putri; Saipul Annur; Choirun Niswah (Jurnal Pendidikan Tambusai, 2025)
This study is motivated by the significance of Melayu Riau customary marriage as a medium for integrating Islamic values and contemporary social identity amidst modernization. The research aims to explore the ritual practices of customary marriage and their impact on social identity formation in the Melayu community. It employs a qualitative approach using library research methods. The population includes academic literature, historical documents, and regulations relevant to the topic, with purposive sampling from 2011-2025. Data collection instruments comprised documentation techniques, with content and descriptive analysis to examine patterns of Islamic value and cultural integration. Findings reveal that Melayu Riau customary marriage preserves Islamic values while adapting to modern demands, fostering a hybrid social identity that is both Sharia-compliant and adaptive. The conclusion emphasizes that this tradition serves as a crucial bridge for cultural and religious harmony and social legitimacy for younger generations, yet strategic support is necessary for sustainable preservation and development.